Curating Research: e-Merging New Roles and Responsibilities in the European Landscape (Conference Report) - Angevaare, Inge (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2009)
On 17 April 2009 LIBER, the Koninklijke Bibliotheek (KB) and the Netherlands Coalition for Digital Preservation (NCDD) co-organised LIBER’s first workshop on digital curation/preservation, providing an introduction to the theme of digital curation and different perspectives on the roles research libraries can and/or must play in keeping the digital records of science safe for future generations. Speakers included Eileen Fenton (Portico), Dale Peters (DRIVER), Maria Heijne (TU Delft Library), Jeffrey van der Hoeven (KB, PARSE.insight) and ninety workshop attendees. The paper includes the conference report and some results of the PARSE.insight online survey into digital preservation practices of LIBER libraries.